Dakwah Anti Ekstremisme Melalui Media Instagram (Analisis Konten Di Instagram Infonusia) - Mohammad Nasrullah; Siti Asiyah; Umdatul Baroroh (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2024)
This Process of information disclosure is very easy to be used by extremist Islam. They aggressively spread propaganda through social media, both in text to audio-visual. This has triggered unrest for the public by looking at the phenomenon that is happening right now, because social media is currently not friendly and leads to wrong understanding. This has become an urgent need for the community, given the extreme upheaval of Islamic extremism to surface to look for pilgrims. This researcher wants to explore the process of making da’wah conten through social media, as well as knowing the standards used in making da’wah content, with the hope that the public will be able to choose correctly which media propagate the noble values of Islam by emanating respect for the people.